14(x+2)=7(2x-3)

Simple and best practice solution for 14(x+2)=7(2x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14(x+2)=7(2x-3) equation:



14(x+2)=7(2x-3)
We move all terms to the left:
14(x+2)-(7(2x-3))=0
We multiply parentheses
14x-(7(2x-3))+28=0
We calculate terms in parentheses: -(7(2x-3)), so:
7(2x-3)
We multiply parentheses
14x-21
Back to the equation:
-(14x-21)
We get rid of parentheses
14x-14x+21+28=0
We add all the numbers together, and all the variables
49!=0
There is no solution for this equation

See similar equations:

| (x=2)(x+12)=(x+16)12 | | -90-x=-43 | | 18x2+9x=0 | | (x)/(5)-(2x)/(3)=(9)/(7)-x | | (x)/(3)+1=5 | | x-25=67 | | (20)(39)=(x+8)(2x-6) | | 3^4x-1=156 | | -59+x=-35 | | (3x-8)/5-(x-1)/4+(7-x)/3=(4-X)/3-(8x-5)/10 | | x+-42=-53 | | 3x-5-2=27 | | (6x-8)=(5x+10) | | -99+x=-149 | | 0.03^x=2.4 | | (3x-1)(3)=4(x+5) | | 24000=24000-300t | | 20=x2x-4 | | 3x-10=50° | | 15=8u-6u | | 15+0.5x=3x | | (3x+9)=(x+9) | | 3g+2(g+2)=2+2*2+2-2g | | 9h-21-21=24 | | -7=w/2-3 | | 4x(7)=10 | | x^-35x+196=0 | | 8x+3+4x+3+90=180 | | P(x)=4x^-1 | | 30/4=100/x | | 192=-y+129 | | 8/11x1/11=-4/11 |

Equations solver categories